SLN and NLC for topical, dermal, and transdermal drug delivery - Souto, Eliana B. (2020)
Introduction: From a biopharmaceutical standpoint, the skin is recognized as an interesting route for drug delivery. In general, small molecules are able to penetrate the stratum corneum, the outermost layer of the skin. In contrast, the delivery of larger molecules, such as peptides and proteins, remains a challenge. Nanoparticles have been exploited not only to enhance skin penetration of drugs but also to expand the range of molecules to be clinically used.Areas covered: This review focus on Solid lipid nanoparticles (SLN) and Nanostructured lipid carriers (NLC) for skin administration. We discuss the selection criteria for lipids, surfactants, and surface modifiers commonly in use in SLN/NLC, their production techniques, and the range of drugs loaded in these lipid nanoparticles for the treatment of skin disorders.Expert opinion: Depending on the lipid and surfactant composition, different nanoparticle morphologies can be generated. Both SLN and NLC are composed of lipids that resemble those of the skin and sebum, which contribute to their enhanced biocompatibility, with limited toxicological risk. SLN and NLC can be loaded with very chemically different drugs, may provide a tunable release profile, can be produced in a sterilized environment, and be scaled-up without the need for organic solvents.